Implementasi Kebijakan Anti Plagiarisme dan Etika Penulisan Ilmiah di Lingkungan Akademik Indonesia - Nasywa, Alika (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The causes of plagiarism are internal factors (within oneself) and external factors. This act of plagiarism is an unethical act, it can occur due to the influence of surrounding environmental factors. The social environment has a big influence on dishonest behavior, namely in the form of social expectations that someone who is considered intelligent is someone who has high grades, gets respect and acceptance in the social environment. Honesty and originality of scientific work, including moral ethics, are included in the realm of character building or character formation. Character building is an effort to build and shape a person's morals to be good. The trend of plagiarism cases that occur in Indonesia is different from cases that occur abroad. In Indonesia it has reached a higher level, namely among educators such as lecturers and even university leaders. This research aims to determine the implementation of anti-plagiarism policies and scientific writing ethics in the Indonesian academic environment. The implementation of anti-plagiarism policies and scientific writing ethics has not been able to maximize originality in the Indonesian academic environment. This activity was carried out as an effort to implement anti-plagiarism policies in the Indonesian academic environment. So that plagiarism prevention measures will be effective if all parties collaborate to support their implementation. The method used in this research is descriptive qualitative. Meanwhile, data collection techniques start from participant observation, document search to in-depth interviews.